2002
DOI: 10.1024/1012-5302.15.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative comparison of physical and mental state during nursing before and after a basic introduction into kinesthetic nursing in a nuclear and radio-therapeutic clinic

Abstract: Competence was already high in the team at the time of the first interview, but even improved by the time of the second interview. This is expressed by the resource-oriented patient-nurse partnership in the process of nursing, by team communication, as well as the heavily weighing discrepancy between knowledge and limited authorisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although much important information in the systematic review of Sedlak-Emperer was reported (purpose, population, intervention, outcome, appraisal tools, study results), others were missing (study protocol, amount of reviewers, procedure of title-abstract- and full text screening) [ 56 ]. The same applies for the study of Christen et al [ 46 ]. Due to the Finnish language in the study of Tamminen-Peter (and a resulting language barrier), assessment of this category was “unclear” [ 48 ].…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Although much important information in the systematic review of Sedlak-Emperer was reported (purpose, population, intervention, outcome, appraisal tools, study results), others were missing (study protocol, amount of reviewers, procedure of title-abstract- and full text screening) [ 56 ]. The same applies for the study of Christen et al [ 46 ]. Due to the Finnish language in the study of Tamminen-Peter (and a resulting language barrier), assessment of this category was “unclear” [ 48 ].…”
Section: Resultsmentioning
confidence: 92%
“…Thirteen studies were appropriate for the qualitative analysis: Two randomized controlled trials [ 47 , 51 ], one cross-over study [ 48 ], one controlled before-after study [ 57 ], three uncontrolled before-after studies [ 46 , 49 , 52 ], three evaluation studies [ 45 , 50 , 53 ], one qualitative study [ 55 ] and two reviews [ 54 , 56 ]. The difference between the before-after studies and the evaluation studies was that outcomes in the evaluation studies were only measured once (at the end of the project), whereas the outcomes of the before-after studies were measured at baseline and at follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations